Jump performance during official matches in elite volleyball players: A pilot study - Lima, R. F.; Palao, J. M.; Clemente, F. M. (Journal of Human Kinetics, 2019)
The purpose of this pilot study was to assess the types and intensity of the jumps that professional male volleyball players executed. Seven male elite volleyball players participated in this study. The sample was composed of 1599 jumps performed in 15 sets of five official matches of the regular season of a professional team. A descriptive pilot study design was implemented to analyze the types of jumps and jump heights by particular playing positions (outside hitters, setter, and middle blockers). The jump height was recorded using an inertial measurement device. No significant differences in the heights of jumps were found between the sets of the matches. Different players` roles had different frequencies for different types of jumps and jump intensities. The data provide reference values of the type of jumps performed, their frequency, and intensity by particular playing positions in competition. The results confirm the need to individualize the practice and training of volleyball players according to the players` roles. Extensive studies are needed to provide more information about repeated jump ability in volleyball players.